Anthropology : the basics - Metcalf, Peter (New York : Routledge, 2005)
A beginner's guide to anthropology, providing information about key concepts and fundamental principles in the field, and including fact boxes.
Encountering cultural difference -- Misunderstanding cultural difference -- Social do's and don'ts -- African political systems -- Anthropology, history, and imperialism -- Culture and language -- Culture and nature -- The end of the tribes -- Culture and the individual -- Critical anthropology.
Includes bibliographical references (p. [207]-212) and index.
Adult
Keywords: Anthropology; Anthropology